Life cycle and hostes of Callosobruchus maculatus (Coleoptera: Bruchidae) - MORENO-R., ALEXANDRA PATRICIA; DUQUE-G., ADRIANA; DE LA CRUZ, JAIME; TRÓCHEZ-P., ADOLFO (Revista Colombiana de Entomología, 2000)
The duration of the different states of the cowpea weevils, Callosobruchus maculatus (F.), were: egg 6.48 days, larva 31,84 days, prepupa 3.41 days, pupa 3,67 days. adult female 11.45 days, adult mate 10,9 days. The female grubs show an oviposition period. with an average of duration, of 10.2 days. A total fecundity of 63.42 eggs and a percentage of the fertility of 46%. Theoretically, the rate of increment by generation for C. maculatus is 32.025, the intrinsic growth rate was 0.830 and the finite rate of the growth or number of times of multiplication of insects population was 2.29, showing 6 generations per year. The study of the life cycles' duration in 6 hosts showed that Cajanus presented 32-40 days and the lentil showed the maximum duratíon. 81-83 days. In the preferable proofs of the insect's oviposition (A y B) was obtained the following order: pea, soybean, chickpea, Cajanus, caupi and lentil and in order to the percentage of the emergence the order obtained was the following chickpea, caupí. soybean, Cajanus, pea, and lentil. The study was done under laboratory conditions, in the Center of Vegetable Diagnostic, Corpoica, Palmira, at 1000 mosl. The average of the temperature was 23.48ºC (minimum 19.15ºC, maximum 29.34ºC) and the average of the relative humidity 74.85%.